Effective Social Media Strategies for Academic Institutions - Nayyar, Ruchi (Indian Journal of Computer Science, 2017)
This paper etches out the most successful social media marketing strategies for academic institutions. Universities and colleges can implement best practices of digital marketing to build brand awareness and trust. Using web analytics, marketers can justify investments in digital advertising. This paper works especially well if readers have some background knowledge about social media,Search Engine Optimization (SEO), Google analytics, and content marketing. Social media marketing is accountable. Marketers can design a measurement strategy to accomplish their goals. One practical challenge universities face is evaluating whether their social engagement efforts are able to meet the fundamental goals of their stakeholders. Statistics derived from analytical tools can guide any university to design more focused campaigns targeting specific audiences. Popular social networking sites including Facebook and Twitter are perceived to contribute more return on investments for online marketing campaigns than many others. Therefore, marketers create campaigns around these two platforms only. This study reveals that an integrated marketing strategy involving multiple platforms such as Facebook, Twitter, GooglePlus, Pinterest, Youtube, Instagram, and Blogs is more effective than any strategy deploying only a single channel at a time.